Adsorption studies and effect of heat treatment on porous glass microspheres. (5th August 2021) - Samad, Sabrin A.; Arafat, Abul; Ferrari, Rebecca; Gomes, Rachel L.; Lester, Edward; Ahmed, Ifty
Abstract: This paper investigates the effect of heat treatment on porous glass microspheres produced via a novel flame spheroidization process, followed by exploring their suitability for dye removal from water. The effect of simple use of smaller porogen (≤5 µm) followed by heat treatment on the overall changes in textural and porosity profiles was quantified. Heat treatment was applied at different temperatures between 510°C and 540°C and cross‐sectional SEM and nitrogen adsorption–desorption confirmed pore sizes had narrowed significantly from microporous (55 ± 8 µm) to mesoporous to macroporous range (≥2 nm) yet retained their interconnectivity. This decrease in pore morphologies led to an increased specific surface area and pore volume (by 51%). In addition, dye separation studies were explored using anionic Acid Red 88 (AR88), utilizing batch and column adsorption experimental processes. This study showed that the heat‐treated microspheres achieved higher dye adsorption rates (i.e., 125 mg/g in batch adsorption studies, while column adsorption studies revealed 153 mg/g and 76 mg/g for flow rates 2.2 ml/min and 0.5 ml/min, respectively) in comparison with the nonheat‐treated microspheres. Furthermore, the dye separation profiles were achieved via electrostatic interaction, hydrogen bonding, and Lewis acid–base interaction, without any internal or external functionalization of the microspheres required.